2018
DOI: 10.3390/polym10010045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dendrigraft Generation on the Interaction between Anionic Polyelectrolytes and Dendrigraft Poly(l-Lysine)

Abstract: Abstract:In this present work, three generations of dendrigraft poly(L-Lysine) (DGL) were studied regarding their ability to interact with linear poly (acrylamide-co-2-acrylamido-2-methyl-1-propanesulfonate) (PAMAMPS) of different chemical charge densities (30% and 100%). Frontal analysis continuous capillary electrophoresis (FACCE) was successfully applied to determine binding constants and binding stoichiometries. The effect of DGL generation on the interaction was evaluated for the first three generations (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 55 publications
0
10
0
1
Order By: Relevance
“…The interactions between oppositely and variously charged polyelectrolytes, cationic poly(‐L‐lysine) (PLL) and variously charged statistical copolymers of acrylamide and 2‐acrylamido‐2‐methyl‐1‐propanesulfonate (PAMAMPS) with charge densities 15–100% were studied by frontal analysis continuous CE (FACCE) . FACCE performed in poly(diallyl dimethyl ammonium chloride) coated capillary in the high ionic strength BGE (12 mM Tris, 10 mM HCl, 305–990 mM NaCl, pH 7.4) enabled determination of binding constants and stoichiometry of the formed complexes.…”
Section: Applicationsmentioning
confidence: 99%
“…The interactions between oppositely and variously charged polyelectrolytes, cationic poly(‐L‐lysine) (PLL) and variously charged statistical copolymers of acrylamide and 2‐acrylamido‐2‐methyl‐1‐propanesulfonate (PAMAMPS) with charge densities 15–100% were studied by frontal analysis continuous CE (FACCE) . FACCE performed in poly(diallyl dimethyl ammonium chloride) coated capillary in the high ionic strength BGE (12 mM Tris, 10 mM HCl, 305–990 mM NaCl, pH 7.4) enabled determination of binding constants and stoichiometry of the formed complexes.…”
Section: Applicationsmentioning
confidence: 99%
“…Equation (3a) was used repeatedly to model the interaction, and in many cases a good linearity was found, at least at higher ionic strength (see the discussion of this problem in Ref. [109]) Recently, a careful investigation of this problem was presented by Lounis et al., [164, 165] who demonstrated that Equation (3a) provides an excellent description of experimental data for the interaction of linear and dendrigraft poly(lysine) with synthetic anionic polyelectrolytes.…”
Section: Fundamentals and Linear Polyelectrolytesmentioning
confidence: 99%
“…92 Colcom, a French start-up, has commercialized a dendrimer-like structure first discovered by Collet et al and known as "lysine dendrigrafts," which display primary amine functionalities along its backbone and surface ( Figure 11). [77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][94][95][96][97][98][99][100][101][102][103][104][105][106][127][128][129][130][131][132][133][134][135][136][137][138] Lysine dendrigrafts are primarily utilized for drug 89 and gene delivery. 107 but have also been investigated for their potential as a coagulant, 108 imaging agent, 95 and substrates for tissue engineering.…”
Section: Hydrophilic Ifdsmentioning
confidence: 99%